PENGARUH TERAPI BEKAM TERHADAP PENURUNAN KADAR KOLESTEROL PADA PASIEN HYPERCHOLESTEROLEMIA DI RUMAH SEHAT AL-HIJAMAAH TAHUN 2014/2015 - Sitti Aulia Hidayat; Salsa Anggeraini; TaufiQul Hidayat (Journal Medical Universitas muhammadiyah Makassar, 2018)
To know the effect of cupping therapy to decrease cholesterol levels in patients at Home Healthy hiperkolestrolemia Al-hijamaah in the year 2014/2015. Research observational analytic-numerical categorical pairs. Samples were hypercholesterolemic patients at Home Healthy Al-hijamaah in 2014/2015. Taken by using non-probability sampling technique with purposive sampling method. The primary data obtained directly from respondents, and analyzed by paired T test. The number of samples involved in this study were 45 respondents. Most of the samples were aged 20-45 years were 28 respondents (62.2%), female 27 respondents (60%), and average cholesterol levels before cupping therapy of 262.84 mg / dl and the average after cupping therapy 239.53 mg / dl. In this study, the results of Test Independent t test t test = 2.64 with p = 0,010 (p 0.05) which means that there are significant differences in cholesterol levels before and after cupping therapy